TEM and FESEM investigation of lanthanum nickelate thin films obtained by chemical solution deposition - Zorica Branković; Dana Vasiljević-Radović; Aleksander Rečnik; Slavko Bernik; Goran Branković; Milica Počuča-Nešić (Processing and Application of Ceramics, 2012)
Lanthanum nickelate (LNO) is a perovskite oxide material with metallic conductivity in a wide temperature range which makes it suitable for application as electrode material for thin films. In this paper LNO thin films were prepared by polymerizable complex method from the diluted citrate solutions. Precursor solutions were spin coated onto Si-substrates with amorphous layer of SiO2. Deposited layers were thermally treated from the substrate side with low heating rate (1 °/min) up to 700 °C and finally annealed for 10 hours. Results of AFM and FESEM showed that films are very smooth (Ra = 4 nm), dense, crack-free and with large square-shaped grains (170 nm). According to FESEM and TEM results the obtained four-layered film was only 65 nm thin. EBSD and XRD analyses confirmed polycrystalline microstructure of the films without preferential orientation. It was concluded that the presence of SiO2 layer on Si substrate prevents epitaxial or oriented growth of LNO.